The Effectiveness of Acid and Base Android-Based Ludo Chemistry Game Media on Students' Cognitive Learning Outcomes - Aulia Khairani; Iswendi Iswendi (Jurnal Paedagogy, 2023)
This research aims to analyze the level of effectiveness of the chemical ludo game on students’ cognitive learning outcomes in class XI SMA/MA. This method of research used a Quasi-Experimental with a non-equivalent control group design. The population of this research was students of class XI MIPA SMAN 3 Tualang. The sampling technique in this research was purposive, so class XI MIPA 1 was selected as the control class and XI MIPA 2 as the experiment class. The research instrument used in this study was the learning achievement test. The data analysis technique used was the N-Gain test, and hypothesis testing using the t-test. The results showed that students’ learning outcomes in the experimental class increased compared to the control class. It was evidenced by the average post-test score of 64.545 for the experimental class and 79.091 for the control class. The results of the N-Gain test for the experimental class were in the high category, namely 0.73 and for the control class, 0.57 in the medium category. The hypothesis test showed that at the real level α = 0.05 with dk = 78, the value of count (5.1413) > table (1.8044). Acid and base android-based ludo chemistry game media effectively improved cognitive learning outcomes of class XI SMA/MA students.